Bank role in preventing money laundering and cyber security - Akbar Ilma, Muhammad; Murtanto, Murtanto; Aryati, Titik (Technium Social Sciences Journal, 2022)
The purpose of this study is to examine the effect of AML disclosure and cyber security on bank performance and to test whether intellectual capital strengthens or weakens the effect of AML disclosure and cyber security on bank performance. This study uses a sample of banking companies listed on the Indonesia Stock Exchange (IDX). The sample used is 41 banking companies listed on the Indonesian stock exchange. The findings of this study are (1) there is an effect of AML disclosure on Bank Performance. (2) there is no influence of cyber security on bank performance. The limitations of this research do not cover all types of banking in Indonesia, there are still many banking companies in Indonesia but they are not listed. The regulatory implications related to money laundering are the implementation of anti-money laundering programs in the financial services sector could be extended become a disclosure.